Presencia en los alrededores de La Plata de Characidium (Jobertina) rachowi y de Hyphessobricon meridionalis sp. nov. (Osteichthyes, Tetragonopteridae) - Ringuelet, Raúl Adolfo (1978)
Characidium (Jobertina) rachowi, known only from Brazil and northern Argentina is reported from Los Talas, in the neighborhood of La Plata. Hyphessobrycon meridionalis sp. nov. is described from the same locality. Anatomical data on both species and a list of the known species of the genus Hyphessobrycon are given.